PERMASALAHAN PEMBENTUKAN ILMU PEMASARAN (Fokus Ekonomi, 2009)
A growing number of academics have questioned the basis and value of marketing principles and have brought into question the credibility of the dominant paradigm of marketing. Marketing thinking is profoundly dominated by the logical empiricist paradigm. It is argued that marketing can be enriched by opening up to alternative paradigm.A review of contemporary literature in the philosophy of science reveals that this canonical conception of science cannot be supported.